Comparison of Mathematics Learning Outcomes of Students Who Are Taught Using Concept Maps with Those Who Are Not in Class X MAN 1 Padang - Eriza, Irvia (Pasundan Social Science Development, 2025)
Mathematics is an essential science in life, yet not everyone enjoys it. Despite its importance, students often struggle with mathematics, perceiving it as difficult and relying on memorization of concepts. To address this, an effective teaching method is needed to help students engage with and improve their learning outcomes. This study applies the use of concept maps in teaching, guiding students to understand the meaning and relationships between formulas. The concept map helps students not only memorize concepts but also see how they are interconnected. The purpose of this study was to determine whether students taught with concept maps had better mathematics learning outcomes compared to those who did not use concept maps. The hypothesis was that students using concept maps would perform better. The research used an experimental design with two groups: an experimental group taught using concept maps and a control group taught without them. The sample consisted of 33 students from each group, selected randomly from a population of 164 students at MAN 1 Padang. Data on learning outcomes were collected using an essay test at the end of the study. The results showed that students in the experimental group performed better. The average score in the experimental group was 74.43, compared to 68.24 in the control group. Additionally, 29 students in the experimental group met the minimum passing criteria, while only 25 in the control group did. The study concluded that using concept maps significantly improved students' mathematics learning outcomes.